Pengaruh Senam Lansia Terhadap Peningkatan Vo2 Max Dan Kecepatan Jalan Lansia - Ammar Arifin, Idris, Dwi Rosella Kumalasari SSt.FT. M.fis, Isnaini Herawati ,SSt.FT. M.Sc (2016)
Background: Elderly is an advanced stage of the process of a life marked by a decrease in the ability of various organs, functions and tubuhsecara natural or physiological systems to be able to adapt to environmental stresses. A sign of the aging process generally will occur at the age of about 60 years. Important problems first, the complaint of the elderly is that they are not capable of running as before. The second important issue, decline in function experienced by the elderly is the respiration system. The decline include decreased the respiratory muscles are the muscles of both a respirator and the main respiratory muscles. Objective: To determine the walking speed of the elderly. To determine the influence of gymnastics elderly to increase walking speed in the elderly. To determine the maximal VO2 in the elderly. To determine the effect of the increase in the elderly gymnastics maximal VO2 in the elderly. Methods: Quantitative research, design researchers used was quasi Experimental Design. The study design was pretest-posttest control group Design.Teknik sampling purposive sampling with inclusion and exclusion criteria of 40 people who were divided into two groups: the experimental group and the control group. Test data analysis with test of Shapiro - Wilk test. Result: The result of data analysis shows the influence of the elderly gymnastics to increase VO2 max and the walking speed of the elderly with a value of p = 0.000 Ho1 and Ho2 rejected, Ha1 and Ha2 accepted. Conclusion: By using research methods with quantitative research, design researchers used is quasi Experiment Design. It was concluded that there is significant influence gymnastics elderly to increased VO2 max and the road speed of the elderly. Keywords: Elderly, VO2 max, walking speed and Gymnastics Elderly.